The young Derrida and French philosophy, 1945-1968 - Baring, Edward, 1980- (Ideas in context, 2011)
"The intellectual history of postwar France often resembles village life. Most of the important academic institutions - the Sorbonne, the Ecole Normale Superieure, the College de France, the Ecole Pratique des Hautes Etudes, even the cafes where Sartre debated with Camus - sit within the same square mile on the left bank of the Seine. This "village" was not only geographically limited. Names recur with surprising regularity: Bachelard, father and daughter, two Merleau-Pontys, as well as numerous Jolys, Lautmans, Pons and Michauds filling up the promotions at the elite centers for higher learning. The founder of Tel Quel, Philippe Sollers, married the philosopher Julia Kristeva; Jacques Lacan married Georges Bataille's widow; his daughter married the Lacanian Jacques-Alain Miller. Pierre Bourdieu, Michel Serres, and Jacques Derrida were schoolfriends before they were philosophical interlocutors and then rivals"--